Tricuspid Valve Endocarditis in a 50 year male non-IV drug user. - Hasan, Azizul; Munwar, Shams; Rahman, Muzibur; Rahman, Mahfuzur; Marium, Anita; Asaduzzaman, Md (Pulse, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/pulse.v5i1.20190 Pulse Vol.5 January 2011 p.44-49